Detection of changes and trends in climatic variables in Bangladesh during 1988–2017. Issue 3 (March 2019) - Khan, Md Hafijur Rahaman; Rahman, Ananna; Luo, Chuanxiu; Kumar, Sazal; Islam, G.M. Ariful; Hossain, Mohammad Akram
Abstract: Due to the importance of climatic variability, an assessment detecting the changes and trends has been carried out over different time series of major climatic variables from the records of meteorological stations over Bangladesh from 1988–2017. Linear regression, the Mann-Kendall test, and Sen's slope method were used to analyze the significant trends and magnitude of the variables' changes, while the Pearson and Spearman rho correlation test have been applied to correlate between the variables. The results show that the average monthly maximum temperature ( T max ) and minimum temperature ( T min ) have increased significantly by 0.35 °C/decade and 0.16 °C/decade, respectively. However, the increase in T max is comparatively higher than T min and caused significant increases in the monthly temperature range (MTR) at a higher rate in winter than in the monsoon season. The trend patterns of T max, T min, and MTR reveal that most of the regions of the country (especially the south-eastern and north-eastern) have been colder during winter and hotter during the monsoon. In contrast, the wind speed (WS) has decreased significantly all over the country and decreased by a higher rate in the north-western (NW) region (monsoon, 0.60 and annual, 0.51 kt/decade) than other regions, while the monsoonal and annual precipitation have decreased by 87.35 mm/decade and 107 mm/decade, respectively. The monsoonal T max and T min (0.47 °C/decade and 0.38 °C/decade, respectively) have increased significantly in the NW; consequently, this region has been warmed by 0.27 °C/decade. The increase in temperature and decrease in WS may cause a decrease in rainfall in the NW region. Humidity changes are not significant except in the monsoon season across the country. Precipitation, WS, and humidity are negatively correlated with the temperature variables. The declination of WS may influence the rising trend in temperature and the falling trend in precipitation and humidity, suggesting the need for further advanced study on the negative effects of climate change in Bangladesh.